Identification of novel KIF11 mutations in patients with familial exudative vitreoretinopathy and a phenotypic analysis - Li, Jia-Kai (Sci Rep, 2016)
KIF11 gene mutations cause a rare autosomal dominant inheritable disease called microcephaly with or without chorioretinopathy, lymphedema, or mental retardation (MCLMR). Recently, such mutations were also found to be associated with familial exudative vitreoretinopathy (FEVR). Here, we report 7 novel KIF11 mutations identified by targeted gene capture in a cohort of 142 probands with FEVR who were diagnosed in our clinic between March 2015 and November 2015. These mutations were: p.L171V, c.790-2A>C, p.Q525*, p.Q842*, p.S936*, p.L983fs and p.R1025G. Phenotypic analysis revealed that all of the affected probands had advanced FEVR (stage 4 or above). Three had microcephaly, and one had chorioretinopathy, which indicated a phenotypic overlap with MCLMR. Two mutations were also found in the families of the affected probands. One parent with a p.R1025G mutation had an avascular peripheral retina and abnormal looping vessels. However, one parent with p.L983fs had normal retina, which indicated incomplete penetration of the genotype. Our results further confirmed that KIF11 is causative of FEVR in an autosomal dominant manner. We also suggest the examination of MCLMR-like features, such as microcephaly, chorioretinopathy, for patients with FEVR and wide-field fundus photography for patients with MCLMR in future practice.